2009
DOI: 10.1124/mol.109.061234
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Heterotrimeric G Protein-Regulated Rho Guanine Nucleotide Exchange Factors

Abstract: Activation of certain classes of G protein-coupled receptors (GPCRs) can lead to alterations in the actin cytoskeleton, gene transcription, cell transformation, and other processes that are known to be regulated by Rho family small-molecular-weight GTPases. Although these responses can occur indirectly via cross-talk from canonical heterotrimeric G protein cascades, it has recently been demonstrated that Dbl family Rho guanine nucleotide exchange factors (RhoGEFs) can serve as the direct downstream effectors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
147
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(154 citation statements)
references
References 141 publications
5
147
0
2
Order By: Relevance
“…Therefore, we asked whether Ga 12/13 competes with Tctex-1 binding, and whether displacement of Tctex-1 by Ga 12/13 may contribute to the activation of GEF-H1. GEF-H1 immune complexes from HEK293T cells expressing GEF-H1, Tctex-1 and Ga 13QL were analysed for the presence of Tctex-1 and Ga 13 . While Tctex-1 was detected in GEF-H1 immunoprecipitates derived from cells expressing GEF-H1 and Tctex-1 alone, expression of Ga 13QL markedly reduced the association of Tctex-1 with GEF-H1 (Fig.…”
Section: P=0024mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we asked whether Ga 12/13 competes with Tctex-1 binding, and whether displacement of Tctex-1 by Ga 12/13 may contribute to the activation of GEF-H1. GEF-H1 immune complexes from HEK293T cells expressing GEF-H1, Tctex-1 and Ga 13QL were analysed for the presence of Tctex-1 and Ga 13 . While Tctex-1 was detected in GEF-H1 immunoprecipitates derived from cells expressing GEF-H1 and Tctex-1 alone, expression of Ga 13QL markedly reduced the association of Tctex-1 with GEF-H1 (Fig.…”
Section: P=0024mentioning
confidence: 99%
“…Ga 12/13 proteins play a well-established role in the activation of RhoGEFs belonging to the regulator of G-protein signalling (RGS) domaincontaining RhoGEF subfamily, which includes p115-RhoGEF, PDZ-RhoGEF, leukemia-associated RhoGEF (LARG) and possibly Lbc-RhoGEF [11][12][13] . Ga 12/13 subunits bind directly to the RGShomology (RH) domain contained within the polypeptide sequences of these GEFs, which is thought to alleviate autoinhibition of their exchange activity.…”
mentioning
confidence: 99%
“…Accordingly, it has been demonstrated that RhoA and RhoC are key promoters of breast cancer invasion and metastasis (11,12). Consistent with the fact that numerous RhoGEFs exist in humans (1), multiple RhoGEFs, such as leukemia-associated RhoGEF (LARG), PDZ-RhoGEF, and myosin II-interacting GEF (MyoGEF), are implicated in promoting breast cancer cell invasion through activation of RhoA and/or RhoC (13)(14)(15).…”
Section: We Have Reported Previously That Nonmuscle Myosin Ii-interacmentioning
confidence: 97%
“…AKAP--Lbc selectively activates RhoA but not other members of the Rho family such as Rac and Cdc42 [22]. PH domains can control the localization and/or the activity of DH domains [231]. A crystal structure of the complex between RhoA--GDP and the AKAP--Lbc--DHPH domain showed that the PH domain is connected with the DH domain by a helical linker and that the switch I and II regions of RhoA bind to two distinct regions of the DH domain.…”
Section: The Interaction Of Akap--lbc and Rhoamentioning
confidence: 99%